2011
DOI: 10.1590/s1516-89132011000300001
|View full text |Cite
|
Sign up to set email alerts
|

Development and reproduction of Podisus nigrispinus (Hemiptera: Pentatomidae) fed with Thyrinteina arnobia (Lepidoptera: Geometridae) reared on guava leaves

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 12 publications
3
15
0
3
Order By: Relevance
“…Vacari et al (2007) observed that the lifespan of female P. nigrispinus fed on D. saccharalis larvae was 17.61 days, unlike the results obtained in this study, and much lower than the results of Oliveira et al (2004a), when they fed P. nigrispinus with T. molitor larvae to P. nigrispinus. The lifespans were also lower than when female P. nigrispinus were fed on larvae of Thyrinteina arnobia (Stoll, 1782) (Lepidoptera: Geometridae) larvae (35.54 days) (Oliveira et al, 2011) and larvae of M. domestica (20.3 days) (Lacerda et al, 2004). Lemos et al (2003) and Oliveira et al (2004a;) also observed that females live longer than males (29.3 days compared to 28.1 days when fed on larvae of Bombyx mori (Linnaues, 1758) (Lepidoptera: Bombycidae) and M. domestica alternately, 67.2 days compared to 49.5 days when fed on T. molitor larvae).…”
Section: Resultsmentioning
confidence: 94%
“…Vacari et al (2007) observed that the lifespan of female P. nigrispinus fed on D. saccharalis larvae was 17.61 days, unlike the results obtained in this study, and much lower than the results of Oliveira et al (2004a), when they fed P. nigrispinus with T. molitor larvae to P. nigrispinus. The lifespans were also lower than when female P. nigrispinus were fed on larvae of Thyrinteina arnobia (Stoll, 1782) (Lepidoptera: Geometridae) larvae (35.54 days) (Oliveira et al, 2011) and larvae of M. domestica (20.3 days) (Lacerda et al, 2004). Lemos et al (2003) and Oliveira et al (2004a;) also observed that females live longer than males (29.3 days compared to 28.1 days when fed on larvae of Bombyx mori (Linnaues, 1758) (Lepidoptera: Bombycidae) and M. domestica alternately, 67.2 days compared to 49.5 days when fed on T. molitor larvae).…”
Section: Resultsmentioning
confidence: 94%
“…(Inayat et al, 2011;Neves et al, 2010;Menezes et al, 2012a). Podisus nigrispinus Dallas, 1851 (Heteroptera: Pentatomidae) é um percevejo encontrado em culturas florestais e agrícolas no Brasil, com eficiência em predar lepidópteros e coleópteros daninhos (Torres et al, 2006;Grazia, 2011;Oliveira et al, 2011;Menezes et al, 2012b). Este predador tem sido criado em laboratório e liberado em programas de controle biológico em culturas como o eucalipto (Zanuncio et al, 2002a), algodão (Medeiros et al, 2000), soja (Ferreira et al, 2008) e tomate .…”
Section: Introductionunclassified
“…lower than that of fifth-instar nymphs and males and females P. nigrispinus fed on Thyrinteina arnobia (Stoll, 1792) (Lepidoptera: Geometridae) with guava leaves (Oliveira et al, 2011). The higher weight of females than males was due to the biomass accumulated by females from the fifth-instar stage, necessary for reproduction.…”
Section: Discussionmentioning
confidence: 99%
“…The weight gain of the females was also related to the ovary development and egg formation (Oliveira et al, 1999;Oliveira et al, 2002). The mean number of eggs per P. nigrispinus female fed with P. xylostella and broccoli (467.90) was higher than with T. arnobia larvae on guava trees (314.90) (Oliveira et al, 2011), Alabama argillacea (Hüebner, 1818) (Lepidoptera: Noctuidae) on cotton (348.10) , and with T. molitor (296.66; 325.00) (Oliveira et al, 2004b;Espindula et al, 2006), Diatraea saccharalis (Fabricius, 1794) (Lepidoptera: Pyralidae) (97.12) (Vacari et al, 2007) and T. arnobia (57.00) on Eucalyptus (Holtz et al, 2006;Holtz et al, 2007). This high number of eggs suggests that the prey P. xylostella and broccoli leaf may have higher nutritional values for the predator P. nigrispinus.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation